2016
DOI: 10.17795/compreped-39741
|View full text |Cite
|
Sign up to set email alerts
|

The Nutcracker Syndrome as a Rare Cause of Chronic Abdominal Pain: A Case Report

Abstract: Introduction: Renal vein entrapment, named nutcracker phenomenon, is a contraction of renal vein between abdominal aorta and superior mesenteric artery. Patients can be asymptomatic or clinically manifested, called nutcracker syndrome. Proteinuria, hematuria, flank pain, varicocele in males and pelvic congestion in females are reported in such patients. Case Presentation: The current report presented an eight-year-old girl with microscopic hematuria and chronic abdominal pain along with short review of anatomy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…4 Pournasiri referred to the disorder as NCS in 1972. 1 Hematuria is a common urinary abnormality with a prevalence of 0.5%-2.0% among school-age children. The prevalence of NCS in children with hematuria is unknown.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…4 Pournasiri referred to the disorder as NCS in 1972. 1 Hematuria is a common urinary abnormality with a prevalence of 0.5%-2.0% among school-age children. The prevalence of NCS in children with hematuria is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…NCS presentation depends on the severity of the LRV hypertension which ends to the rupture of the thinwalled septum between the small veins and the collecting system in the renal fornix. 1,4 The diagnostic criteria of NCS have not been established yet, and there is no simple procedure for a definitive diagnosis at present. 7 Although it has been suggested that selective left renal venography is the standard procedure for the diagnosis of NCS, we did not use this technique in our patients because of its invasiveness and the burden of radiation that …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations